Peran Keluarga Sebagai Dukungan Sosial Bagi Mahasiswa Perantau Sosiologi Uin Sunan Gunung Djati Bandung - Nerin Puspita Dewi; Naailah Hidaayatun Nasywa; Sri Damayanti (Jurnal Keluarga Sehat Sejahtera, 2026)
This study aims to understand the role of the family as a social support system for students living away from home, with an emphasis on the quality of the bond between students and their parents. This study employs a qualitative approach using a case study method among Sociology students at UIN Sunan Gunung Djati Bandung. Data were collected through in-depth interviews with students living away from home and their parents, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results indicate that families provide various forms of social support, such as emotional, instrumental, informational, and appreciative support. However, the quality of the bond between students and their parents varies, which influences how this support is perceived. Students with strong relationships feel the support more acutely, while less close relationships make the support feel less tangible, even though it is still provided. These findings suggest that the quality of the bond plays a crucial role in determining how strongly social support is felt by students living away from home.